Synthesis of poly(hydroxyethyl methacrylate)‐b‐poly(propylene glycol)‐b‐poly(hydroxyethyl methacrylate)reactive block copolymer with controlled reactivity for toughening multifunctional epoxy resin. Issue 37 (23rd July 2022) - Zhu, Hong; Tang, Bing; Lv, Yadong; Huang, Yajiang; Yang, Qi; Li, Guangxian; Kong, Miqiu
Abstract: Multifunctional epoxy resins are inherently brittle due to the extremely high cross‐linking density, thus the enhancement in the toughness is rather important for the industrial application. In this work, a reactive poly(hydroxyethyl methacrylate) ‐b‐ poly(propylene glycol) ‐b‐ poly(hydroxyethyl methacrylate) (PHEMA‐PPG‐PHEMA) is synthesized by using an atom transfer radical polymerization to toughen trifunctional diglycidyl 4, 5‐epoxy cyclohexane‐1, 2‐dicarboxylate (TDE‐85). A controllable system is constructed, in which the reaction temperature of TDE‐85 with the hydroxyl of PHEMA‐PPG‐PHEMA is lower than with the curing agent. As a result, both heterogeneous and homogeneous structures can be formed in composites through controlling reaction temperature. It is found that the toughness of composites with the heterogeneous structure is effectively improved without sacrificing the tensile strength, tensile modulus, and glass transition temperature. Specifically, the mode‐1 critical stress intensity factor and critical strain energy release rate of TDE‐85/10 wt% PHEMA‐PPG‐PHEMA are increased to 0.77 MPam 1/2 and 146 J/m 2, respectively, which are effectively enhanced by 32.8% and 70.3%. This can be ascribed to combined toughening effects from the cavitation of the PHEMA‐PPG‐PHEMA phase, the matrix shear yielding, and the enhanced interface bonding strength due to the reaction between TDE‐85 and PHEMA‐PPG‐PHEMA. Thus, this study paves a novel strategy to improve the toughness of epoxy resin by controlling the curing reaction. Abstract :